Feasibility Studies on Enhancement of Mechanical and Water Purification Properties of Pervious Concrete Using Granite Dust as Partial Cement Replacer - Abhinaya M; Rangasamy Parthiban; Sivakumar N (International Journal of Sustainable Construction Engineering and Technology, 2024)
Usage of pervious concrete in pavements, roof tops and other such applications has increased recently. This type of concrete aids in infiltration of excessive run-off in an ecofriendly manner. In this study, improvement of pervious concrete properties using industrial waste Granite Dust (GD) as partial cement replacement is analysed. Percentage of replacements so considered is in range of 0.5 – 2% and compared with reference mix properties. Results of the analysis show that replacement using GD for upto 1% increases the strength of the sample. Therefore, in the mix with 1% GD, a maximum strength of 13.5 MPa is observed which is 41% higher than that of mix without replacement. While GD replacement enhances the density, reduction in porosity, infiltration capacity, and water absorption is observed consequently. This variation in property is reasoned by the micro-filling effect of GD. In addition, dried powder samples are analysed using SEM/EDAX, FTIR, and XRD. Further analysis of water treatment ability of the pervious concrete specimens considering six parameters namely TSS, COD, BOD, TOC, TP, and TN show that GD replacement can potentially increase the pollutant removal ability of the mix than that of reference mix with maximum removal achieved for TP (77.9%) in sample with 2% replacement.